Seneca’s Etna: the Epicurean principle of multiple explanations, anti-sublimity and the Stoic sage (Ep. 79) - Myrto Garani (Dictynna, 2023)
In his Letter 79 (probably written in c. AD 64) Seneca asks his addressee, Lucilius, who was then serving as procurator of Sicily, to send him a report on his travels around the island, including information specifically on Charybdis and Lucilius’ climb up Mount Etna. In addition to this “scientific tourism”, Seneca encourages Lucilius to attempt a new poem on Etna, “the venerated theme of every poet” (Ep. 79.5) and not to be deterred from doing so by the fact that there are already prominent literary works that offer remarkable descriptions of Etna. In my paper, I will first briefly discuss the implications of Seneca’s choice to single out Vergil’s and Ovid’s works as the specific volcanic intertexts against which not only Lucilius, but also he himself will initiate the process of literary emulation. In this connection, I will also explore the significance for Seneca of the fact that Lucretius’ volcanic passages -to which Seneca does not refer overtly- are the dominant intertexts for both Vergil and Ovid. I will then discuss the principle of multiple explanations and the notion of the sublime, two prevailing thematic themes that the Epistle 79 shares with the Natural Questions (in particular Books 3 and 4a) and which are conditioned by Seneca’s intertextual reception of Lucretius and Ovid.